Implementasi Prinsip Hukum Islam dalam Kegiatan Pemasaran: Antara Teori dan Realitas Lapangan - Ilmia Rofi; Sriwahyuni Sriwahyuni (Institut Agama Islam Miftahul Ulum Pamekasan, 2024)
Marketing is a crucial component of business systems that determines the success of distributing goods and services from producers to consumers. However, in practice, marketing activities often face ethical dilemmas, especially when intense business competition drives marketers to neglect moral values in pursuit of targets. In the Islamic context, marketing is not merely assessed from an economic perspective but also through the lens of Sharia law, which emphasizes honesty (ṣidq), trustworthiness (amānah), justice, and the prohibition of deceit (tadlīs) and ambiguity (gharar). This study aims to examine how these Islamic legal principles are implemented in modern marketing practices. The research employs a qualitative method based on library research, using both normative and linguistic approaches. The findings reveal a gap between the theoretical ideals of Sharia-compliant marketing and real-world practices, where manipulative tactics that contradict Islamic ethics are still prevalent. Therefore, integrating spiritual values into marketing is essential to establish a business practice that is not only profit-oriented but also blessed and sustainable.